PEMBUATAN APLIKASI PENAJAMAN GAMBAR UNTUK PENGOLAHAN CITRA DIGITAL - Santoso Setiawan; Ahmad Firdaus (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2014)
The image or images are inseparable in everyday life. For certain purposes, the image can be processed into the form of data or digital image. Many image processing programs that are market, but most of these programs are still very difficult to use, where ordinary people do not get to use it. From this background, the sharpening of images has created an application that aims to allow users to perform image processing or manipulation, so that the picture is unclear or sharp can be clarified or refined into high-resolution images. This image sharpening application making use of the method or technique to sharpen the edges of objects that create the picture will look different than before. The program used in the making of this application is Delphi 7 with the Windows operating system. This image sharpening application has been tested on several images to a low resolution and can produce images with the sharpness effect that can be set by the user and can be stored using a different file name with the name of the original file.